Formuła ważenia zasad prawa jako mechanizm usuwania ich kolizji na przykładzie koncepcji Roberta Alexego - Maroń, Grzegorz (My University, 2015)
This paper raises one of the issues correlated with the problems of legal principles, i.e. construction of the so-called weighing formula. The basic purpose of the paper was to verify usability of the formula as a tool enabling deciding in case of collisions of legal principles according to requirements of rationality and objectivism. The Author decided to get an answer to this question by analyzing the theory of legal principles by Robert Alexy. Confronting, on the one hand, the concept of the law principles, as optimizing orders and the extended pattern of weighing, with the practice of judicial decisions by the Federal Constitutional Court of Germany, on the other one, he concluded that the mathematical form of the weighing formula is of limited use. He found justified the opinion of J. Habermas that implementation of the weighing pattern is able to generate a solution (to specify the priority relation between colliding principles), but it fails to justify correctness of such a solution.
FORMULA OF WEIGHING LEGAL PRINCIPLES